Analysis of Plasmonic Structure using Finite Element Method - M Nasar, Norasikin; Abdul-Kahar, Rosmila; Esa, Fahmiruddin Esa; Amir Hamzah, Nor Shamsidah (Journal of Science and Technology, 2018)
Plasmonic structure was investigated by modelling the different shape of v-groove shape and curve shape in three dimension (3D) using Finite Element Method (FEM). We simulate and compare the shape with electric and magnetic wave propagation in term of total electric energy and total magnetic energy using gold as a metal material and glass as a dielectric material. The result of the reflection and transmission of transverse electric (TE) wave and transverse magnetic (TM) wave with the angle of incidence are shown depending on the shape of plasmonic structure by using analytic solution based on Fresnel equation.